Reaksi Pasar Sebelum dan Sesudah Kenaikan Harga BBM pada Perusahaan yang Listing di Bursa Efek Indonesia (BEI) - Riskhy Tia Femianita; Nadia Asandimitra (BISMA (Bisnis dan Manajemen), 2018)
Fuel price increase that happened on June 2013 for gasoline and diesel fuel. Fuel price increase policy should taken by goverment in order to decrease hyper subsidy that effected to deficit budget. This researchs aim is to dict the differences market reaction between before and after fuel price increase with measure abnormal return and trading volume activity. Analysis method that use in this research is event study with event period during 21 days by using market adjusted model. The result of this reseacrh with one sample t test are the average abnormal return is significantly positive values around the date of announcement of fuel price increases. The result of this reseacrh with paired sample t-test there are differences in average abnormal return and average trading volume activity significantly before and after the announcement of fuel price increases. It shows that the market reacts to the announcement of fuel price increases.